Activin receptor-like kinase 7 promotes apoptosis of vascular smooth muscle cells via activating Smad2/3 signaling in diabetic atherosclerosis - Shengchuan Cao; Shengchuan Cao; Shengchuan Cao; Shengchuan Cao; Qiuhuan Yuan; Qiuhuan Yuan; Qiuhuan Yuan; Qiuhuan Yuan; Qianqian Dong; Qianqian Dong; Qianqian Dong; Qianqian Dong; et al. (Frontiers in Pharmacology, 2022)
Vascular smooth muscle cells (VSMCs) is a vital accelerator in the late phase of diabetic atherosclerosis, but the underlying mechanism remains unclear. The aim of our study was to investigate whether activin receptor-like kinase 7 (ALK7)-Smad2/3 pathway plays an important role in VSMC apoptosis of diabetic atherosclerosis. It was shown that ALK7 expression was obviously elevated in the aorta of ApoE−/− mice with type 2 diabetes mellitus. Inhibition of ALK7 expression significantly improved the stability of atherosclerotic plaques and reduced cell apoptosis. Further experiments showed that ALK7 knockdown stabilized atherosclerotic plaques by reducing VSMC apoptosis via activating Smad2/3. Our study uncovered the important role of ALK7-Smad2/3 signaling in VSMCs apoptosis, which might be a potential therapeutic target in diabetic atherosclerosis.